Modulating Alkyl Groups in Copolymer to Control Ion Transport in Electrolyte‐Gated Organic Transistors for Neuromorphic Computing - Junho Sung; Minji Kim; Sein Chung; Yongchan Jang; Soyoung Kim; Min‐Seok Kang; Hee‐Young Lee; Joonhee Kang; Donghwa Lee; Wonho Lee; Eunho Lee (Small Structures)
Electrolyte‐gated organic synaptic transistors (EGOSTs) have shed light on their potential in bioelectronics and neuromorphic computing. Numerous research have been studied to modulate their electrochemical doping performance and formulate a simple approach to control iontronics through the side‐chain modulations; however, the effects of alkyl groups as side moieties have not been studied in detail on EGOSTs. Herein, the structural and electrical properties of conjugated polymers are systematically controlled through copolymerization with two different‐alkyl group‐derived monomers for enhancing the nonvolatile characteristics of EGOSTs. The relationships between crystal orientation and electrochemical doping states of conjugated copolymers, which varied with the different copolymerization ratios, are revealed. Also, the behavior of biological synapses, including paired‐pulse facilitation, spike timing‐dependent plasticity, and long‐term potentiation/depression, are successfully simulated. In this study, new avenues are opened for the implementation of neuromorphic devices through side‐chain engineering by showing that the alkyl chain modulates the doping performance.